Safety and efficacy of compound methyl salicylate liniment for topical pain: A multicenter real-world study in China - Guo, Jie; Hu, Xiaolei; Wang, Jing; Yu, Bin; Li, Juan; Chen, Jianting; Nie, Xiaoli; Zheng, Zhijian; Wang, Shixuan; Qin, Qun (Frontiers in Pharmacology, 2022)
Compound methyl salicylate liniment (Ammeltz) is composed of various components, such as methyl salicylate, menthol, camphor, chlorpheniramine maleate, and thymol. It was approved for listing in China in 2011. The purpose of this phase Ⅳ clinical trial was to evaluate the safety and efficacy of Ammeltz in a real-life environment in China. Adverse events and adverse drug reactions were used to assess the safety of the monitored drugs. Visual analog scale (VAS) scores were evaluated to assess the severity of pain and the pain relief rate was used to evaluate the efficacy of the study drug. Of 3,600 subjects enrolled, 3,515 (97.64%) subjects completed the study and 85 (2.36%) terminated the study prematurely. A total of 277 adverse events occurred in 258 subjects (7.28%). The most common adverse events included upper respiratory infections (130 cases, 3.67%), local pruritus (17 cases, 0.48%), and diarrhea (12 cases, 0.34%). A total of 50 (1.41%) subjects experienced 58 adverse drug reactions. The most common adverse drug reactions included local pruritus (17 cases, 0.48%), a burning sensation at the application site (10 cases, 0.28%), and irritation at the application site (local) (7 cases, 0.2%). No adverse reactions were identified as new adverse drug reactions. The majority of adverse drug reactions were mild (48 cases, 1.36%), and no severe adverse drug reactions occurred. The subjects experienced significant pain relief after using Ammeltz. The pain relief rate was 47.11% ± 23.13%, and in 2,769 cases (78.31%) the drug was effective in pain relief. After excluding subjects who used drugs that could affect the efficacy of the study drug, the subgroups of subjects experienced significant pain relief after using Ammeltz (mean VAS scores: 5.31 vs. 2.77; Day 7 ± 1 vs. Baseline; p < 0.0001). The pain relief rate was 47.34% ± 23.00%, and 2,612 subjects (78.75%) experienced effective pain relief. In conclusion, Ammeltz is safe and effective in real-life use. It can significantly relieve soft tissue pain caused by shoulder and neck pain, back pain, or muscle pain. No new adverse drug reactions were found in our multicenter real-world study.